Alleviation of extensive visual pathway dysfunction by a remyelinating drug in a chronic mouse model of multiple sclerosis. (29th January 2021) - Sekyi, Maria T.; Lauderdale, Kelli; Atkinson, Kelley C.; Golestany, Batis; Karim, Hawra; Feri, Micah; Soto, Joselyn S.; Diaz, Cobi; Kim, Sung Hoon; Cilluffo, Marianne; Nusinowitz, Steven; Katzenellenbogen, John A.; et al.
Abstract: Visual deficits are among the most prevalent symptoms in patients with multiple sclerosis (MS). To understand deficits in the visual pathway during MS and potential treatment effects, we used experimental autoimmune encephalomyelitis (EAE), the most commonly used animal model of MS. The afferent visual pathway was assessed in vivo using optical coherence tomography (OCT), electroretinography (ERG), and visually evoked cortical potentials (VEPs). Inflammation, demyelination, and neurodegeneration were examined by immunohistochemistry ex vivo. In addition, an immunomodulatory, remyelinating agent, the estrogen receptor β ligand chloroindazole (IndCl), was tested for its therapeutic potential in the visual pathway. EAE produced functional deficits in visual system electrophysiology, including suppression of ERG and VEP waveform amplitudes and increased signal latencies. Therapeutic IndCl rescued overall visual system latency by VEP but had little impact on amplitude or ERG findings relative to vehicle. Faster VEP conduction in IndCl‐treated mice was associated with enhanced myelin basic protein signal in all visual system structures examined. IndCl preserved retinal ganglion cells (RGCs) and oligodendrocyte density in the prechiasmatic white matter, but similar retinal nerve fiber layer thinning by OCT was noted in vehicle and IndCl‐treated mice. Although IndCl differentially attenuated leukocyte and astrocyte staining signal throughout the structures analyzed, axolemmal varicosities were observed in all visual fiber tracts of mice with EAE irrespective of treatment, suggesting impaired axonal energy homeostasis. These data support incomplete functional recovery of VEP amplitude with IndCl, as fiber tracts displayed persistent axon pathology despite remyelination‐induced decreases in latencies, evidenced by reduced optic nerve g‐ratio in IndCl‐treated mice. Although additional studies are required, these findings demonstrate the dynamics of visual pathway dysfunction and disability during EAE, along with the importance of early treatment to mitigate EAE‐induced axon damage. Abstract : To understand deficits in the visual pathway during MS and potential treatment effects, the most commonly used animal model of MS, experimental autoimmune encephalomyelitis (EAE), was used. EAE‐induced retinal ganglion cell loss, axon demyelination, and VEP related increased latency were mitigated by the remyelinating drug indazole chloride. Measuring visual function and recovery in the presence of novel therapies can be used to screen more effective therapies that will protect axons, stimulate axon remyelination and prevent ongoing axon damage.